Effect of electroosmotic flow of aqueous suspension of nanosilica on the properties of carbonated concrete. Issue 1 (18th May 2017) - Redaelli, E.; Torabian Isfahani, F.; Lollini, F.; Wu, H. T.; Bertolini, L.
Abstract : The paper investigates the possibility to use electroosmosis to transport nanosilica (NS) particles inside carbonated concrete, in order to exert a filler effect and enhance its durability performance. This method aims to extending possible beneficial effects of NS to existing reinforced concrete structures, where the presence of a carbonated layer of concrete is very likely. Injection tests were performed with electrochemical cells on carbonated concrete discs with water/cement (w/c) ratios of 0.50, 0.55 and 0.65, using a NS aqueous suspension at the anode. The results indicated that a flow did occur through the concrete disc and it was directed from the anode towards the cathode. A linear relationship between flux and applied voltage gradient was obtained, which is typical of electroosmotic phenomena. The bulk properties of concrete, such as density, water absorption and sorptivity, were not affected by the injection tests, whilst electrical resistivity increased indicating a mild 'sealing' effect on the surface. Also microstructural analyses highlighted the local presence of NS that decreased the local porosity close to the surface. Abstract : Electroosmosis is used to inject nanosilica particles dispersed in aqueous suspension inside carbonated concrete with the aim of improving its durability properties. Bulk properties of concrete, like density and water absorption, are not affected by the treatment, nor is sorptivity, whilst concrete electrical resistivity increases and porosity decreases after the treatment, indicating a mild 'sealing' effect on the surface.